Efficiency analysis of clear forestry for Radiata pine plantations in Chile - Meneses, Mario; Guzmán, Sergio (Bosque (Valdivia), 2000)
The efficiency of the implicit silvicultural process was analyzed in a sample of 30 stands. Efficiency was defined as the capacity of the process to produce a stand with a high potential of clear wood production for a given site, that is, a stand with a high PLI (Pruned Log Index). This was done firstly by visualizing the individual effects of pruning and thinning in the configuration of stand potential, and secondly by determining the combined effect of the interaction between these activities and the site in reaching a certain PLI level. This confirmed a high relation between records of stand management and their PLI. Appropriate silviculture recommendations were derived from the analysis to apply to each site type.